1997
DOI: 10.1007/s002640050116
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Staphylococcus aureus slime-producing strain variants to biomaterials used in orthopaedic surgery

Abstract: Summary. The adherence of Staphylococcus aureus to biomaterials used in orthopaedic surgery (polymethylmethacrylate, fresh bone, steel and titanium alloys) and to glass was studied in vitro at 1,2,6, 80 and 510)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 20 publications
1
30
0
2
Order By: Relevance
“…The selection of the bacterial isolate b a 2µ used for the implant before colonization and bone infection is of particular importance for establishing osteomyelitis. SP strains strongly adhere to various biomaterials and resist phagocytosis or antibiotic treatment in vitro, colonize tissues, resist antibiotics and cause chronic infections in vivo (Baselga et al 1993, Gracia et al 1997, Monleón et al 1997, König et al 1998, Amorena et al 1999). Such bio lm-associated problems have contributed to the use of this type of strains in chronic disease models (Deighton et al 1996, Gracia et al 1997, Hanssen and Rand 1998, König et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the bacterial isolate b a 2µ used for the implant before colonization and bone infection is of particular importance for establishing osteomyelitis. SP strains strongly adhere to various biomaterials and resist phagocytosis or antibiotic treatment in vitro, colonize tissues, resist antibiotics and cause chronic infections in vivo (Baselga et al 1993, Gracia et al 1997, Monleón et al 1997, König et al 1998, Amorena et al 1999). Such bio lm-associated problems have contributed to the use of this type of strains in chronic disease models (Deighton et al 1996, Gracia et al 1997, Hanssen and Rand 1998, König et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria that attach to a surface and grow as a biofilm are protected from the killing action of antibiotics. The protective mechanisms at work in biofilms appear to be distinct from those that are responsible for conventional antibiotic resistance (Gracia et al 1997, Sheldon 2005. The biofilm can act as a shield for the bacteria, making it difficult for them to be reached and destroyed by antibiotic drugs.…”
Section: Small-colony Variants (Scvs)mentioning
confidence: 99%
“…In this context and using highly adherent strains, we have observed that S. aureus in vitro adherence and biofilm formation on inert or mammalian cell surfaces is associated with (i) exopolysaccharide production (6,23); (ii) rough colony morphology phenotype in Congo red agar (CRA) (6); (iii) higher resistance to phagocytosis (32); (iv) lower susceptibility to antibiotics when forming biofilms (2); (v) higher capacity to attach to different surfaces and biomaterials used in orthopedic surgery, causing osteomyelitis (16); and (vi) higher capacity to colonize the ovine mammary gland, causing mastitis (6). In addition, active immunizations with exopolysaccharides extracted from a highly adherent S. aureus isolate have been shown to trigger protective immunity against mastitis (3).…”
mentioning
confidence: 99%